Re-imagining risky health behaviour as salutogenic practice. (13th November 2019) - Cross, R
Abstract: Background: Much has been written about the problematic risky health practices that some young women in western cultures engage in defined as, for example, drinking alcohol to excess, smoking and taking drugs. Conversely the literature is more limited with regards to the meaning that young women attribute to such 'unhealthy' practices. Exploring and understanding meaning is important in order to design more effective health promotion interventions. Methods: This paper will present findings from 22 in-depth interviews with young women aged 18 - 14 years in post-compulsory education who were invited to talk about health and risk. Discourse analysis was used to explore the data drawing on feminist and governmentality perspectives. Results: The data presented complex constructions of risk taking in health drawing on intertwined discourses of moralism, healthy citizenship, idealised femininity and health as a gendered pursuit. However, the young women also constructed their 'unhealthy' practices in alternative, more agentic, resistant and philosophical ways. Conclusions: Based on these latter findings it is proposed that some risky health behaviours should be interpreted as salutogenic rather than pathogenic in nature. Subjective constructions of risky health practices as salutogenic should be taken into account in risk communication strategies and interventions in public health. Key messages: Exploring and understanding meaning is important in order to design more effective health promotion interventions. Subjective constructions of risky health practices as salutogenic should be taken into account in risk communication strategies and interventions in public health.